Changes in Productivity and Composition of Output in Building Construction, 1972-1982 - Schriver, William R.; Bowlby, Roger L. (The Review of Economics and Statistics, 1985)
William R. Schriver, Roger L. Bowlby, Changes in Productivity and Composition of Output in Building Construction, 1972-1982, The Review of Economics and Statistics, Vol. 67, No. 2 (May, 1985), pp. 318-322